Pengaruh Gaya Kepemimpinan Situasional Terhadap Kinerja Pegawai (Studi Pada Dinas Pendapatan Kabupaten Fak-fak) - Lapi, Yusuf (Fakultas Ekonomi, UIN Maliki Malang, 2010)
This research is intended to find out the influence of elements in situational leadership style toward the performance of the Dinas Pendapatan Kabupaten Fak-fak employees. The elements to be analysed include the instructive leadership behavior (X1), consultative leadership behaviour (X2), participative leadership behaviour (X3), and delegacies leadership behaviour (X4), as independent variables, and the performance as dependent variable. The objectives of the research are to analysed the influence of the situational leadership style which consist of instructive leadership behaviour (X1), consultative leadership behaviour (X2), participative leadership behaviour (X3), and delegacies leadership behaviour (X4) toward performance of the Dinas Pendapatan Kabupaten Fak-fak employees and to analysed the dominant influence leadership behaviour toward performance of the Dinas Pendapatan Kabupaten Fak-fak employees. The whole employees, 73 person, of Dinas Pendapatan Kabupaten Fak-fak is considered as the population, and all of the employees as a sample by using census technique. The result of the research shows that the instructive leadership behaviour (X1), consultative leadership behaviour (X2), participative leadership behaviour (X3), and delegacies leadership behaviour (X4) has no significant influences toward performance, and the Ho at first hypothetic is rejected. its means the delegacies leadership behaviour has significant influence toward performance. Answering the second hypothetic found the regression coefficient delegacies leadership behaviour has the value of 0.626, and significantly value 0.046. So the delegacies leadership behaviour has positive and significant value toward performance, and the second hypothetic is rejected.